Inorganic Lead Toxicology - Jiří Patočka; Karel Černý (Acta Medica, 2003)
Lead is a health hazard for all humans. Especially children under the age of six are most at risk for lead poisoning. Lead toxicity causes hematological, gastrointestinal, and neurological dysfunction. Symptoms are usually noted with blood lead greater than 2 micromoles/L. Severe or prolonged exposure may also cause chronic nephropathy, hypertension, and reproductive impairment. Lead inhibits some enzymes, alters cellular calcium metabolism, stimulates synthesis of binding proteins in kidney, brain, and bone, and slows down nerve conduction. Acute lead poisoning is relatively infrequent and results from ingestion of acid soluble lead compounds or inhalation of lead vapors but chronic exposure to low levels of the metal is still a public health issue, especially among some minorities and socioeconomically disadvantaged groups. Lead has been used since prehistoric times, and has become widely distributed and mobilized in the environment. Exposure to and uptake of this non-essential element have consequently increased. Both occupational and environmental exposures to lead remain a serious problem in many developing and industrializing countries and a public health problem of global dimensions.